ULTRASOUND-GUIDED TREATMENT OF CHRONIC KNEE PAIN DUE TO OSTEOARTHRITIS: DIAGNOSTIC AND THERAPEUTIC APPROACH BASED ON THE TYPE OF PAIN - Hayak Pereira Lopes, Maykon (Health and Society, 2025)
Knee osteoarthritis (OA) is a prevalent cause of chronic pain and disability. Pain phenotyping (inflammatory, mechanical, and neuropathic) guides more effective interventions. Ultrasound (USG) allows diagnostic stratification (synovitis, effusion, periarticular changes) and accurately guides intra-articular injections (corticosteroid, local anesthetic, hyaluronic acid), genicular nerve blocks, and Valeix injections. This review summarizes the diagnostic basis, technique, and pharmacological choices guided by USG, discussing evidence and practical applications.